The Roman Church Against the State Power - Polak, Tomasz (Poznańskie Studia Slawistyczne, 2016)
This article emphasizes the important but rarely analyzed aesthetic-political dimension of the relationship between the Roman Catholic Church and the state. The author synthetically discusses the development of the inner consciousness of the Church of Rome (in its relation to the power) in three nodal epochs: in the Church of Leo the Great and his successors, in the Church of the Gregorian reform and of Innocent III and in the nineteenth-century Church. According to the author’s conclusion: it can be shown that the key to understanding the relationship of the Church of Rome to the state power is the phantasmatic belief in the superiority of own ecclesiastical authority over every other power, a belief developed originally in the self-awareness and in the emotional and aesthetic self-emplacement of the great popes of the 5th and 6th centuries.